The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1007/bf00014558
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an ABA-responsive osmotin-like gene during the induction of freezing tolerance in Solanum commersonii

Abstract: We have isolated a cDNA (pA13) of an ABA-responsive gene from suspension cultures of Solanum cultures of Solanum commersonii. The deduced amino acid sequence of pA13 cDNA revealed 89 and 91% identity with tobacco osmotin and tomato NP24 protein, respectively. The accumulation of the transcript corresponding to pA13 cDNA was regulated by ABA, cold temperature, and low water potential treatments. Cold-induced accumulation of the pA13 transcript was partially suppressed by fluridone, an ABA synthesis inhibitor, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 30 publications
1
48
0
1
Order By: Relevance
“…Many PR-type proteins are JA-and/or ET-inducible (150), and their occurrence can be further modulated by abscisic acid (7,89,113,181). Whereas in Arabidopsis a distinction between the SA-inducible PR-1, -2, and -5, and the JA/ET-inducible PR-3, -4, and -12 seems clear (143), in tobacco it has been demonstrated that different members within the same protein family are differentially regulated by SA and JA/ET (97,128).…”
Section: Signaling In the Induction Of Defense-related Proteinsmentioning
confidence: 99%
“…Many PR-type proteins are JA-and/or ET-inducible (150), and their occurrence can be further modulated by abscisic acid (7,89,113,181). Whereas in Arabidopsis a distinction between the SA-inducible PR-1, -2, and -5, and the JA/ET-inducible PR-3, -4, and -12 seems clear (143), in tobacco it has been demonstrated that different members within the same protein family are differentially regulated by SA and JA/ET (97,128).…”
Section: Signaling In the Induction Of Defense-related Proteinsmentioning
confidence: 99%
“…However, the activity of GST-ABI2 was maxithe ABI2 mRNA appeared to be more weakly expressed in leaves. Figure 6B shows that the ABU and ABI2 mRNAs were induced by sorbitol, an experimental treatment that mimicks conditions of low water potential (Zhu et al, 1993). The abundance of both transcripts was reduced in the ABAdeficient abal mutant ( Figure 6B), suggesting that endogenous ABA upregulates the expression of these mRNAs.…”
Section: Comparative Analysis Of Abil-1 and Abi2-1 Mutantsmentioning
confidence: 98%
“…Among stress proteins are osmotin and osmotin-like proteins that have also been classified as members of plant PR type-5 proteins (Singh et al, 1989;BOI et al, 1990;Zhu et al, 1993Zhu et al, , 1995. It has been demonstrated that tobacco osmotin gene expression is activated by ABA, NaC1, wounding, vira1 infection, and ethylene (LaRosa et al, 1992;Nelson et al, 1992).…”
mentioning
confidence: 99%